Introducing Social Dermatology - Elisabeth M.M. Christensen; Gregor Jemec; Ditte Marie L. Saunte; Ole Steen Mortensen (Acta Dermato-Venereologica)
Increasing evidence supports the idea that social determinants of health, e.g., educational attainment, employment, and community context, directly affect health status. Researchers are also beginning to explore the impact of social factors on skin diseases, though no formalized research field, to the authors’ knowledge, provides a structured framework for such practice. In this article, the novel global research field of ”Social Dermatology” is introduced to structure academic knowledge in dermatology. The aim is to outline how this paradigm shift could transform both clinical practice and scientific research. The field will explore subjects studied within the medical field of Social Medicine, adapting and applying them to the context of dermatology. Specifically the article will address the social determinants of health in dermatology, and elaborate on human functioning as an approach to a more comprehensive understanding of health in people with skin diseases. This approach enables the integration of rehabilitative aspects, with the International Classification of Functioning (ICF) guiding research and clinical practice to promote more equitable and patient-centred care. To address methodological and communicative opportunities it is suggested that a theoretical web-based social incubator be developed. A formal agreement on the values, interests, and challenges of this new field is needed for a sustainable research effort.